ENVIRONMENTAL IMPACTS OF RENEWABLE ENERGY TECHNOLOGIES IN THE TRANSPORTATION SECTOR: A BIBLIOMETRIC REVIEW - Song, C. C. K.; Shah, M. A. M.; Sivasankar, T. A.; Yatim, S. N. J. M. (Journal of Engineering and Technology (JET), 2025)
Renewable energy sources have gained substantial significance concerning the depletion of non-renewable energy resources and the adverse environmental consequences associated with their consumption. However, the possible impact of shifting from non-renewable energy to renewable energy sources is still debatable. Moreover, the broadening development of renewable energy technologies mainly in the transportation sector determines the viability of renewable energy is scarce. Hence, this study aims to provide an understanding of the impact of Renewable energy technology on the environment and to evaluate the viability of renewable energy implementation in the transportation sector. This bibliometric review provides insights on advancing renewable energy technology, and current evidence present from different perspectives. The extensive search of this study revealed that the negative impacts of renewable energy can be mitigated through careful planning and implementation of renewable energy projects, such as conducting thorough environmental impact assessments and developing appropriate waste management. The environmental impact associated when electrical generation relies on fossil fuel is worse, while renewable energy can substantially reduce emissions, for example in electric vehicles. This literature review provides fundamental evidence that highlights the strong viability of renewable energy specifically in electric vehicle applications in terms of economic, social, environmental, and technical aspects.